The Digital Division of Labor: Socially Constructed Design Patterns of Amazon Mechanical Turk and the Governing of Human Computation Labor - Berlo, Kurt; Wagner, Oliver (Momentum Quarterly, 2015)
In this paper we examine the preservation strategies of the German energy regime following the transition approach developed by Geels. From a multi-level perspective it can be observed: Innovations take place in niches and have to overcome the obstacles and the persistence of the conventional fossil-nuclear energy regime. By means of an empirical analysis it can be concluded that – with regard to the local electricity grids – the established regime significantly delays the decentralisation process required for a transformation of the energy structures. Besides, it is shown that Stadtwerke (public utilities) are important key actors for the German Energiewende (energy transition) in their function as local energy distributors and meet a variety of requirements to promote a fundamental structural change. The trend towards remunicipalisation and the re-establishment of public utilities reveal the desire to further strengthen the scope of local politics. In this context we refer to policy goals and to promising strategies for changing the old regime elements.